WHAT DO YOU THINK ABOUT AI vs HUMAN MADE ART? - Noorhaslina, Senin; Azwan, Abidin; Siti Shahida, Kamel; Chuah, Kee Man; Salmiah, Abdul Hamid (UNIMAS Publisher, 2024)
Recently, artificial intelligence has emerged as a powerful tool for generating art, blurring the lines between human and machine creativity. The year 2023 is said to be the year for artificial intelligence (AI), and has raised concerns among artists and designers. This participatory artwork invites visitors to explore this artistic divide and challenge their perceptions of what constitutes ‘real’ art. The artwork consists of paired images - one generated by an AI algorithm and the other created by a human artist. Visitors will be asked to examine the artworks and identify which image they believe was generated by AI and which was created by humans. By encouraging visitors to engage with and critically analyze each image, the artwork aims to highlight the similarities and differences between human and AI artwork. This artwork hopes to spark a conversation about AI’s role in art and encourage visitors to reflect on their own creative processes.